2016
DOI: 10.1038/srep25237
|View full text |Cite
|
Sign up to set email alerts
|

GPR40 agonist ameliorates liver X receptor-induced lipid accumulation in liver by activating AMPK pathway

Abstract: Hepatic steatosis is strongly linked to insulin resistance and type 2 diabetes. GPR40 is a G protein-coupled receptor mediating free fatty acid-induced insulin secretion and thus plays a beneficial role in the improvement of diabetes. However, the impact of GPR40 agonist on hepatic steatosis still remains to be elucidated. In the present study, we found that activation of GPR40 by its agonist GW9508 attenuated Liver X receptor (LXR)-induced hepatic lipid accumulation. Activation of LXR in the livers of C57BL/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…Strawberries from ve developmental stages were harvested and collected. Developmental stages were dened as small green (SG, seven days post-anthesis (DPA)), big green (BG, 14 DPA), white fruit (WF, 21 DPA), turning (TU, 28 DPA), and red fruit (RF, 35 DPA), as described by Li et al 21 The calyxes and pedicels of strawberry were removed and both strawberry achenes and receptacle were frozen in liquid nitrogen immediately before stored at À80 C. Three independent biological replications at three harvest times (Dec 5th 2015, Jan 5th 2016 and Feb 5th 2016) were prepared for each developmental stage using mixed achene and receptacle tissues from twenty ve individual strawberries for subsequent analyses.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strawberries from ve developmental stages were harvested and collected. Developmental stages were dened as small green (SG, seven days post-anthesis (DPA)), big green (BG, 14 DPA), white fruit (WF, 21 DPA), turning (TU, 28 DPA), and red fruit (RF, 35 DPA), as described by Li et al 21 The calyxes and pedicels of strawberry were removed and both strawberry achenes and receptacle were frozen in liquid nitrogen immediately before stored at À80 C. Three independent biological replications at three harvest times (Dec 5th 2015, Jan 5th 2016 and Feb 5th 2016) were prepared for each developmental stage using mixed achene and receptacle tissues from twenty ve individual strawberries for subsequent analyses.…”
Section: Plant Materialsmentioning
confidence: 99%
“…[14][15][16][17][18][19] For strawberry, several research have been carried out to describe the proteomic changes in fruit ripening, 5,14 varietal difference, 20 strawberry allergen, 17 as well as response to environmental stress stimuli. 21,22 However, the relationship between the protein changes and the carbohydrate metabolism during strawberry ripening and development remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the expression of CRABP1 enhanced the activation of the LXR pathway. It is known that the activation of the FXR-RXR and PPAR-RXR pathways suppresses the accumulation of LDs, while the activation of the LXR-RXR pathway results in an increase in the abundance of LDs (15)(16)(17). Thus, the results from our bioinformatics analyses and the reporter assays collectively suggest that the expression of CRABP1 may result in the accumulation of LDs in hepatocytes.…”
Section: Resultsmentioning
confidence: 59%
“…However, there were several studies demonstrated that AMPK inhibited LXRα to prevent lipid accumulation in HepG2 cells (43,44). This discrepancy may be due to the different characteristic properties between pathological cell models, which suggests AMPK may have a selective regulation on LXRα in different pathological process.…”
Section: Discussionmentioning
confidence: 99%